Pendampingan Penyusunan Laporan Keuangan Pada KPRI Karya Praja Bakorwil I Madiun - Suharni, Siti; Rochman, Fatchur (Universitas Merdeka Madiun, 2020)
Entity Financial Accounting Standards Without Public Accountability (SAK ETAP) that are used for entities without public accountability. SAK ETAP is an entity that does not have significant public accountability and publishes general purpose financial statements for external users such as owners who are not directly involved in business management, creditors, and credit rating agencies. For this reason, KPRI Karya Praja needs to understand and compile financial reports according to these regulations. The purpose of this community service is to assist the KPRI Karya Praja management in preparing financial reports in accordance with SAK ETAP and the Cooperative Law, namely by providing assistance. The benefit of this assistance is that the KPRI Karya Praja management is expected to understand the presentation and preparation of the correct financial statements in accordance with SAK ETAP and the Cooperative Act. The method used by the socialization of SAK ETAP and the Cooperative Act was continued with assistance in preparing financial statements. The results of this activity provide knowledge and understanding to the administrative, bookkeeping and treasurer sections on the basics of bookkeeping, code adjustments and account classification based on Financial Accounting Standards ETAP and Cooperative Law and provide assistance in the preparation of correct financial statements in accordance with ETAP Financial Statements and Laws. - About Cooperatives.Â Keywordsâ€”: Assistance; Preparation of Financial Statements.